Adrenal myelolipoma: An incidental and rare benign tumor in children - Shibsankar Barman; Kartik Chandra Mandal; Madhumita Mukhopadhyay (Wolters Kluwer Medknow Publications, 2014)
Myelolipoma is a rare benign tumor of adrenal gland and rarer in children. Myelolipoma contains adipose tissue and myeloid precursor producing white blood cells (WBC), red blood cells (RBC) and megakaryocytes. Asymptomatic tumor does not require treatment whereas symptomatic tumor needs operation. We are reporting a rare adrenal myelolipoma in a child with review of literature.